Cultural Manifestation and Ethnic Tourism: Hospitality in the Urban Public Space (Global Journal of Management and Business Research, 2019)
Considered an ethnic neighborhood, boosted by the occupation of Italian immigrants in the late 19th and early 20th centuries, Bela Vista (also known as Bexiga) is the scene of cultural manifestations that expresses the vitality in the use of public space, becoming a tradition of the city of São Paulo. The neighborhood as a place of hospitality, gathers a set of ten cultural events that were catalogued over the years 2015 and 2016. This article focuses on one of those cultural events, the Italian festivity of Nossa Senhora Achiropita (Our Lady Achiropita). A celebration that by 2018 had been taking place for 92 years. Its aspects and dynamics were analyzed in order to identify the practices of sociability and commensality -treated in this study as dimensions of hospitality -as well as the potential of the neighborhood for ethnic tourism. Characterized as an exploratory research, the methodology of oral history was conducted via interviews with active participants or residents of the neighborhood, and through on site observation and bibliographical and documentary surveys. Among the results, the festive vocation of the neighborhood stands out as it shelters ethnic groups as well as cultural, popular and spontaneous manifestations, which are the locus of hospitality and touristic practices.
Keywords: hospitality in the city; cultural manifestation; public space; sociability; commensality; ethnic tourism